2010
DOI: 10.1021/jz100730q
|View full text |Cite
|
Sign up to set email alerts
|

Isolating the Spectral Signatures of Individual Sites in Water Networks Using Vibrational Double-Resonance Spectroscopy of Cluster Isotopomers

Abstract: We report the spectral signatures of water molecules occupying individual sites in an extended H-bonding network using mass-selective, double-resonance vibrational spectroscopy of isotopomers. The scheme is demonstrated on the water heptamer anion, (H2O)7¯, where we first randomly incorporate a single, intact D2O molecule to create an ensemble of isotopomers. The correlation between the two OD stretching frequencies and that of the intramolecular DOD bending transition is then revealed by photochemical modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Electronic mail: dhlaria@cnea.gov.ar including polar molecules, as well as ions, including excess protons and electrons. [20][21][22][23][24] Since water clusters are normally generated via adiabatic expansions of aqueous vapors that bring their temperature down to the range of ∼100 K or below, one must anticipate that nuclear quantum fluctuations should manifest in a more vivid fashion. 25 Further, since the characteristic vibrational and librational frequencies of water molecules depend on their hydrogen bonding environment, it has long been appreciated that the impact of quantum effects should vary with this environment.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: dhlaria@cnea.gov.ar including polar molecules, as well as ions, including excess protons and electrons. [20][21][22][23][24] Since water clusters are normally generated via adiabatic expansions of aqueous vapors that bring their temperature down to the range of ∼100 K or below, one must anticipate that nuclear quantum fluctuations should manifest in a more vivid fashion. 25 Further, since the characteristic vibrational and librational frequencies of water molecules depend on their hydrogen bonding environment, it has long been appreciated that the impact of quantum effects should vary with this environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, some experimental evidence 17 18 19 20 21 22 and theoretical studies 23 have shown the nonadiabatic effects of vibration/electron coupling on flat metal and some metal nanoparticle surfaces 10 24 , questioning the general applicability of the approach. This problem is even more complicated on the surfaces of catalytic metal nanoparticles, as the electronic properties can vary with particle size 25 and surface sites 26 .…”
mentioning
confidence: 99%
“…Later, improvements in experimental techniques allowed direct comparison with theoretical results. Photoelectron spectroscopy [18][19][20][21][22][23][24] and vibrational spectroscopy [25][26][27][28][29] techniques have been used to garner information about the structural and electronic properties of water cluster anions. These experiments have provided data for the vertical detachment energy (VDE) of small water clusters.…”
Section: Introductionmentioning
confidence: 99%